(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2026)
In this paper I propose as a general objective to analyze certain legal and political aspects of the Argentine laws of due obedience and full stop, from an interdisciplinary perspective, which combines analytical tools of conceptual history and political philosophy. In specific terms, I will proceed to develop three concatenated argumentative steps, namely: a) to explain the content, scope and context of the issuance, justification and repeal of said norms; b) to reconstruct certain considerations made by prominent specialists in history and political philosophy on the subject and its adjacencies; and c) to offer certain reflections of my own, from a republican reflexive perspective of politics and the political. In short, having as an analytical excuse the rereading of the processes of justification and legal annulment of those two regressive laws in the field of human rights, I will try to identify two national Argentinian current approaches in the field of human rights, which are part of a corrosive dyad of the political, which we will call populist decisionism and technocratic libertarianism.